Perancangan E-Kuisioner menggunakan CodeIgniter dan React-Js sebagai Tools Pendukung Penelitian - Ismail, Ismail; AlBahri, Fauzan Putraga (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The development of questionnaires that can capture usability problems in each case is expected to be more effective and efficient. At present, the use of e-questionnaires has evolved with the use of technologies such as the emergence of monkey surveys, type forms, google forms, Zoho surveys, and gizmo surveys that can be used to facilitate the work of creating, distributing and retrieving survey feedback online. This research tries to build an e-questionnaire model using Codeigniter and react-js which can be used as an alternative while prioritizing the appearance of end-users by adopting the Google form service but having features by being able to add questions in the form of multimedia and also being able to disseminate information on survey results with the concept of sharing datasets to various digital online sources. The methodology used in the research to be carried out is the DSRM (Design Science Research Method) method and at the research, the stage consists of; problem identification, defining objects and solutions, design and development, implementation, evaluation, and conclusion. This research resulted in an e-questionnaire application that can be used as an alternative while prioritizing the appearance of end-users by adopting the Google form service but has features that can add questions in the form of multimedia and can also disseminate survey results with the concept of sharing datasets to various digital sources. online with the use of the Codelnigter and React-Js framework can improve effective appearance while maintaining system security. It is hoped that the e-questionnaire can increase the distribution of research data in the form of electronic datasets and can be fully used as a reference for researchers in Indonesia, especially AMIK Indonesia.